Investigation into the microbial flora of healing and non-healing decubitus ulcers. - Daltrey, D C (1981)
Seventy-four pressure lesions in fifty-three geriatric patients were observed at weekly intervals to determine the bacterial flora and the healing index of each lesion, expressed as initial area of lesion (cm2) - final area of lesion (cm2) divided by time in days. The micro-organisms which caused infection included Staphylococcus aureus, Proteus mirabilis, Pseudomonas aeruginosa, Bacteroides fragilis and Bacteroides asaccharolyticus. Many lesions contained a mixed flora. P mirabilis and Ps aeruginosa were associated with necrotic (p less than 0.005) and enlarging (p less than 5 x 10(-7)) lesions. Bacteroides spp were associated with necrotic lesions (p less than 0.05). The presence of S aureus in a lesion was not associated with any particular trend in healing index. The implications of the microbiological findings are discussed.